Are neonatal mortality rates increased in stand‐alone birthing center births compared with hospital births?. Issue 6 (June 2018) - Waits, John B.; Murawska, Aleksandra; Burwell, Lenord; Cade, Arnelya; Smith, Lacy
Abstract : EVIDENCE‐BASED ANSWER : Neonatal mortality rates do not differ when low‐risk patients deliver in an alternative birthing setting within a hospital or in a stand‐alone birthing center compared with a hospital‐based obstetric unit (SOR: B, meta‐analysis of RCT and quasi‐RCTs and 2 cohort studies). However, when home births are grouped with stand‐alone birthing centers there is an associated increase of 1.5 perinatal deaths per 1, 000 deliveries (SOR: B, cohort study).